POSTMODERNIST DECONSTRUCTION OF PUSHKIN'S TEXT AS AN IRONIC ELEMENT OF RUSSIAN SCIENCE FICTION - Kuchinsky A. Yu. (International Journal of Literature and Language Studies, 2026)
This article examines examples of the deconstruction of Pushkin's text in the works of contemporary Russian science fiction writers, reflecting, among other things, the characteristics of postmodernist poetics.